Analysis of Illusions and Imagery in Plato’s “Allegory of the Cave” - Gurung, Raj Kumar; Rai, Ram Prasad (RR Interdisciplinary Journal, 2024)
This paper examines the signs, symbols and images of Plato’s “The Allegory of the Cave” and discusses the difference between the inner and outer worlds and power politics. It also analyses the images and symbols of this text from political as well as philosophical points of view. The inside and outside of the cave signify the human’s reality and prospects. The findings show the cave's shadows, which the prisoners observe daily from inside the cave. And when one prisoner comes out and sees the outer world, he gets disillusioned by the sunlight, the ultimate truth. The cave symbolizes the two worlds: the dark and bright sides of a human world. There has not been sufficient research work in semiotics and allegorical presentation. The study's main objective is to interpret the underlying meanings of the images and symbols of the text and attempts to see the intended meanings to enhance academia as all the scholars may not be able to comprehend the allegorical meanings. The symbolic interpretation can go into the depth of meanings, whereas surficial interpretation may educate the masses superficially. The research is based on these questions: What is the difference between symbolic interpretation and superficial explanation? How is a symbolic interpretation more authentic than a general interpretation? The study employs Chandler’s (2017) semiotic theory and allegorical interpretations.